American Images of Canada: Canadian Muslims in US Newspapers, 1999-2014. - Vucetic, Srdjan (American Review of Canadian Studies, 2016)
How do American news media portray Canadian Muslims? Using a sample of 386 discrete newspaper articles published between January 1, 1999, and December 31, 2014, in The Buffalo News, Tampa Bay Times, The New York Times, The Wall Street Journal, The Washington Post, and USA Today, this article investigates the portrayal of Canadian Muslims in these publications through a combination of content and discourse analyses. Three findings stand out: first, the overall tone of the coverage was neutral or ambiguous rather than either systematically positive or systematically negative; second, a tendency to construct Muslims as social outsiders was common even in articles coded as positive; third, the Canadian Muslim experience was viewed through the prism of discourses on American exceptionalism, and above all the idea that assimilation always trumps multiculturalism.